Myofascial release as a means of increasing the power capabilities of powerlifters - Korichko, A. V.; Samoilov, V. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to increase the effectiveness of the training process of beginner powerlifters through the use of myofascial release exercises.